Auditory processing in the human cortex: An intracranial electrophysiology perspective. Issue 4 (12th April 2017) - Nourski, Kirill V.
Abstract : Objective: Direct electrophysiological recordings in epilepsy patients offer an opportunity to study human auditory cortical processing with unprecedented spatiotemporal resolution. This review highlights recent intracranial studies of human auditory cortex and focuses on its basic response properties as well as modulation of cortical activity during the performance of active behavioral tasks. Data Sources : Literature review. Review Methods : A review of the literature was conducted to summarize the functional organization of human auditory and auditory‐related cortex as revealed using intracranial recordings. Results: The tonotopically organized core auditory cortex within the posteromedial portion of Heschl's gyrus represents spectrotemporal features of sounds with high temporal precision and short response latencies. At this level of processing, high gamma (70–150 Hz) activity is minimally modulated by task demands. Non‐core cortex on the lateral surface of the superior temporal gyrus also maintains representation of stimulus acoustic features and, for speech, subserves transformation of acoustic inputs into phonemic representations. High gamma responses in this region are modulated by task requirements. Prefrontal cortex exhibits complex response patterns, related to stimulus intelligibility and task relevance. At this level of auditory processing, activity is strongly modulated by task requirements and reflects behavioral performance. Conclusions: Direct recordings from the human brain reveal hierarchical organization of sound processing within auditory and auditory‐related cortex. Level of Evidence: Level V